Improving Patient Safety Through the Design and Development of a Computerized Provider Order Entry for Parenteral Nutrition Linked to a Barcode Medication Administration Record...The 16 World Congress of Medical and Health Informatics: Precision Healthcare through Informatics (MedInfo2017) was held in Hangzhou, China from August 21st to 25th 2017 - Jáuregui, Oscar I.; Bruchanski, Lucila; Lede, Daniel A. Rizzato; Otero, Carlos M.; Luna, Daniel R. (Studies in Health Technology & Informatics, 2017)
Among adverse events related to medication errors, the defects in parenteral nutrition administration pose a special threat to patient safety. Two high impact strategies to reduce these errors require implementing a Computerized Provider Order Entry and the use of bedside bar-code verification prior to medication administration. In this study, we share the deep field analysis of the current workflow performed to include inpatient bedside barcoding verification for parenteral nutrition administration in a large academic health center. Then, we propose a process optimization and a new parenteral nutrition ordering tool embedded in the prescription module. Structuring physicians’ ordering and the bar-code verification of administration can increase patient safety. The next steps would involve the creation of a Clinical Decision Support System to improve patient nutrient goals.